Distribution and Spatial Segregation of Shopping Centers in Cancun, Quintana Roo (1979–2019) - Fonseca Chicho, Edgar Elias; Chávez Alvarado, Rosalía; Camacho Sanabria, José Manuel (Universidad Pedagógica y Tecnológica de Colombia, 2020)
This paper aims to analyze the distribution of shopping malls and their consequent segregation in Cancun, Quintana Roo, which has seen an increase in the construction of these properties in recent decades. The method is carried out in two phases: the first, a field survey that groups shopping centers by type of anchor store and the second, the characterization of these properties based on their location. This resulted in five distributions that allow understanding the spatial segregation for three areas of the city in the period between 1979 (first shopping center) and 2019. The results confirm spatial preferences for a territory with a neoliberal perspective that prioritizes the satisfaction of commercial needs of walk-in customers, locating the best centers in exclusive places for the floating population that visits the tourist area and the citizens who inhabit the neighborhoods with the highest quality of life. It is concluded that the distribution of shopping centers has helped to exacerbate the segregated territory that characterizes Cancun.